Metal Oxide for Fast Adsorption System in the Methylene Blue Removal - Ulfa, Maria; Oktaviani, Sukmaningrum Latifah; Mulyani, Bakti; Sholeha, Novia Amalia (Universitas Gadjah Mada, 2025)
Rapid adsorption systems utilizing metal oxide-based materials represent a promising technology to address adsorption challenges, particularly for the effective removal of methylene blue (MB). These systems enhance the continuous MB elimination process by leveraging metal oxide (MO)-based adsorbents with high accessibility and optimized adsorption conditions. The preparation process involves selecting metal oxides with high surface area and strong adsorbate affinity, ensuring efficient interaction with MB. Process parameters such as adsorbent dosage, contact time, temperature, pH, initial concentration, waste volume, and pressure are modified to develop a rapid and sustainable system for MB removal. This configuration enables efficient application in water treatment, achieving faster and more effective MB degradation. Moreover, the scalability of MO-based adsorbents ensures low-cost production and broad applicability, further supporting sustainable waste management. This review critically evaluates experimental findings from various studies on MO-based materials in rapid adsorption systems, highlighting their potential for large-scale implementation in wastewater treatment to mitigate environmental pollution.